The Importance of Church Management and Administration in Supporting Effective Ministry and Congregation Growth - Dondokambey, Martha Agustin; Husen, Aprilliano; Tumiwa, Krueger Kristanto (Proskuneo: Journal of Theology, 2025)
Church management and administration play a vital role in supporting the effectiveness of ministry and congregational development. As an organization serving the community, the church not only needs a solid spiritual foundation, but also good management in order to function optimally in achieving its goals. This article aims to reveal the importance of church management and administration and how it can strengthen the church's ministry and mission in an increasingly complex and dynamic context. This study uses a qualitative method with a descriptive analytical design, which utilizes literature studies as the main data collection technique. This study identifies various concepts and basic principles of holistic church management, as well as their application in church management practices. This article specifically discusses the role of management in managing church resources, such as human resources, finances, and physical church facilities. In addition, efficient church administration can improve services to the congregation, facilitate effective communication between church leaders and the congregation, and strengthen the church's organizational structure to achieve mission goals. The impact of implementing good management and administration is reflected in the increase in the operational efficiency of the church, which ultimately supports more stable and sustainable congregation growth. This article also provides insight into the importance of church leaders who have managerial skills to carry out administrative and ministry tasks professionally. In conclusion, this study confirms that good church management and administration not only strengthens ministry, but is also the key to accelerating the achievement of the church's mission amidst the challenges of the times